Factors affecting the occurrence of proximal endoleak after endovascular abdominal aortic repair for abdominal aneurysms. Issue 11 (November 2020) - Mazzaccaro, Daniela; Mazzeo, Girolomina; Zuccon, Gianmarco; Modafferi, Alfredo; Malacrida, Giovanni; Righini, Paolo C.; Marrocco-Trischitta, Massimiliano M.; Nano, Giovanni
Objective: This retrospective study was performed to assess the clinical and radiological variables associated with proximal type IA endoleak (EL) in patients treated with elective endovascular repair for abdominal aortic aneurysms. Methods: The chi-square test, t-test, and logistic regression analysis were performed as appropriate. A P value of <0.05 was considered statistically significant. Results: The data of 79 patients were analyzed. No mortality occurred. During follow-up (median, 28.5 months; interquartile range, 12.8–43.0 months), 10 patients developed type IA EL. In the logistic regression analysis, undersizing of the endograft diameter by <10% significantly affected the occurrence of type IA EL. When the diameter was used for measurements, less oversizing was significantly associated with a higher risk of type IA EL. When the area was used for measurements, oversizing of >20% significantly affected the occurrence of type IA EL. Conclusion: When sizing endografts, a discrepancy was noted between the measurements of the diameter and area of the proximal neck. The area might represent a more accurate measurement than the axial diameter to optimize the proximal sealing and lower the risk of developing type IA EL.